2019
DOI: 10.1080/07418825.2019.1666903
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabis Effect on Crime: Time-Series Analysis of Crime in Colorado and Washington State

Abstract: Previous studies based on relatively weak analytical designs lacking contextualization and appropriate comparisons have reported that the legalization of marijuana has either increased or decreased crime. Recognizing the importance for public policy making of more robust research designs in this area during a period of continuing reform of state marijuana laws, this study uses a quasi-experimental, multi-group interrupted time-series design to determine if, and how, UCR crime rates in Colorado and Washington, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…This finding challenges the argument made by the opponents of legalization that marijuana legalization would increase crime (Trilling, 2016). As previously mentioned, there exist competing views about whether legalization would increase or decrease crime, and the available limited evidence specifically examining the impact of recreational marijuana legalization on crime is mixed and inconclusive (Lu et al, 2019). However, the results of this study suggest that marijuana legalization in neighboring states may not work against the states that have not legalized in terms of its impact on crime, as we did not detect any increases in the rates of multiple types of crimes in border counties of the nonlegalized states neighboring Colorado and Washington.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding challenges the argument made by the opponents of legalization that marijuana legalization would increase crime (Trilling, 2016). As previously mentioned, there exist competing views about whether legalization would increase or decrease crime, and the available limited evidence specifically examining the impact of recreational marijuana legalization on crime is mixed and inconclusive (Lu et al, 2019). However, the results of this study suggest that marijuana legalization in neighboring states may not work against the states that have not legalized in terms of its impact on crime, as we did not detect any increases in the rates of multiple types of crimes in border counties of the nonlegalized states neighboring Colorado and Washington.…”
Section: Discussionmentioning
confidence: 99%
“…In another study examining the impact of both medical and recreational marijuana outlets on crime, Hughes et al (2020) found that both types of marijuana outlets were positively related to increases in rates of a variety of crimes and neighborhood disorder in Denver. As scholars have reasoned, the criminogenic effect of recreational marijuana dispensaries is largely attributable to the fact that marijuana sale is a cash-and-carry business, which exposes both the business and customers to criminal victimization (Freisthler et al, 2017;Lu et al, 2019). Deriving from the routine activity theory is the argument that marijuana dispensaries create opportunity for the convergence of motivated offenders and suitable targets at the same place and time (Boggess et al, 2014;Glensor & Peak, 2004;Morrison et al, 2014;Wright & Decker, 2011).…”
Section: Marijuana Legalization and Crime: The Unsettled Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Early assessments of the impacts of cannabis legalization on (mostly US-based) population-level crime found that it is either not associated with differences, or rather associated with slight decreases in the incidence of specific types of (e.g., property, violent) crimes, when compared to non-legalization states. Thus, current evidence does not point to criminogenic effects attributable to liberalization policies (Brinkman & Mok-Lamme, 2019;Dragone et al, 2019;Lu et al, 2019;Maier et al, 2017;Morris et al, 2014;Shepard & Blackley, 2016). These outcomes are important towards public healthand safety-related considerations for different cannabis control options, and so warrant further thorough examination.…”
Section: Cannabis and Crimementioning
confidence: 96%
“…robbery and aggravated assault). At the state-level, Lu et al (97), comparing rates of crime in Washington and Colorado to states not legalizing cannabis, found some immediate increases in crime at the point of recreational legalization. Moreover, Lin et al (98) conducted a non-peer reviewed quasi-experimental difference-in-difference analysis to study the potential effect of cannabis use on domestic violence by exploiting municipal and temporal variations in the enactment of recreational cannabis laws in Denver-Aurora-Lakewood Metropolitan Statistical Area from 2011 to 2016.…”
Section: Support From Cannabis Legalization Literaturementioning
confidence: 99%